Anisotropic constitutive model incorporating multiple damage mechanisms for multiscale simulation of dental enamel. (September 2016) - Ma, Songyun; Scheider, Ingo; Bargmann, Swantje
Abstract: An anisotropic constitutive model is proposed in the framework of finite deformation to capture several damage mechanisms occurring in the microstructure of dental enamel, a hierarchical bio-composite. It provides the basis for a homogenization approach for an efficient multiscale (in this case: multiple hierarchy levels) investigation of the deformation and damage behavior. The influence of tension–compression asymmetry and fiber–matrix interaction on the nonlinear deformation behavior of dental enamel is studied by 3D micromechanical simulations under different loading conditions and fiber lengths. The complex deformation behavior and the characteristics and interaction of three damage mechanisms in the damage process of enamel are well captured. The proposed constitutive model incorporating anisotropic damage is applied to the first hierarchical level of dental enamel and validated by experimental results. The effect of the fiber orientation on the damage behavior and compressive strength is studied by comparing micro-pillar experiments of dental enamel at the first hierarchical level in multiple directions of fiber orientation. A very good agreement between computational and experimental results is found for the damage evolution process of dental enamel. Abstract : Highlights: Anisotropic constitutive model is developed for finite deformation of dental enamel. Multiple damage mechanisms and their interaction of enamel are captured explicitly. 3D micromechanical simulations are conducted for the numerical homogenization. The tension–compression asymmetry and fiber–matrix interaction are accounted for. The predicted strengths for different fiber orientations are validated.